WITH INTEREST: $450B. - KELLEY, LORA (New York Times, 2026)
The article reveals that U.S. imports of computers, semiconductors and computer accessories critical to the artificial intelligence (AI) data centers being built across the country topped 450 billion dollars in 2025, but which also contributed to the country's trade deficit.